Hubungan Paritas Ibu Dengan Kejadian Anemia Pada Ibu Hamil Di Puskesmas Sewon II Bantul Yogyakarta - Annisa Rahmah; Widy Nurwiandani; Istri Bartini; Retno Heru Setyorini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Hemorrhage is a significant contributor to maternal mortality in Indonesia. Theprimary cause of hemorrhage during pregnancy is anemia, which occurs when pregnantwomen have a hemoglobin level of less than 11 g/dL. Parity is a factor that influences theoccurrence of anemia. The prevalence of anemia at Health Center Sewon II is still relativelyhigh.Objective: The objective of this study is to determine the relationship between the parity ofworking pregnant women and the occurrence of anemia in pregnant women at Health CenterSewon II Bantul Yogyakarta. Method: This study is a quantitative study using an observational analytic method. Thepopulation of this study includes all pregnant women at Health Center Sewon II. The samplefor the study consists of all working pregnant women at Health Center Sewon II, totaling 47respondents. The sampling technique used in this study is total sampling. Data analysisincludes univariate and bivariate analysis using the Chi-square test.Result: The results of the study indicate a p-value of 0.473 >0.005, suggesting that there isno significant relationship between the parity of working pregnant women and the occurrenceof anemia in pregnant women at Health Center Sewon II Bantul Yogyakarta. The lack of arelationship maybe attributed to various factors such as demographic location, respondentcharacteristics, and environment. Based on the statistical test results with a p-value of 0.473,it can be concluded that there is no relationship between the parity of working pregnant womenand the occurrence of anemia at Health Center Sewon II Bantul, Yogyakarta.Keywords: Anemia, Parity, Pregnant women